Uterus transplantation in France: for which patients?. (October 2016) - Huet, S.; Tardieu, A.; Filloux, M.; Essig, M.; Pichon, N.; Therme, J.F.; Piver, P.; Aubard, Y.; Ayoubi, J.M.; Garbin, O.; Collinet, P.; Agostini, A.; et al.
Abstract: Objective: Uterine infertility (UI), which can be caused by a variety of congenital or acquired factors, affects several thousand women in Europe. Uterus transplantation (UTx), at the current stage of research, offers hope for these women to be both the biological mother and the carrier of their child. However, the indications of UTx still need to be defined. The main aim of the study was to describe the different etiologies of UI and other data as marital and parental status from women requesting UTx who contacted us in the framework of a UTx clinical trial. Secondarily, we discussed the potential indications of UTx and their feasibility. Study design: This is an observational study. Results: Of a total of 139 patients with UI, 105 patients (75.5%) had uterine agenesis, making it the leading cause of UI in this sample. Among the patients with uterine agenesis, 25% had a solitary kidney and 44.7% had undergone vaginal reconstruction. Peripartum hysterectomy, hysterectomy for cancer, and hysterectomy for benign pathologies accounted for 9.4%, 7.2% and 5% of cases, respectively. Less common causes of UI included complete androgen insensitivity syndrome (2.2% of patients) and prenatal diethylstilbestrol exposure (0.7%). Approximately 14% of the women already had at least one child and 66% were in a couple living together for at least 2 years. Conclusion: UTx is still under evaluation and further research is under way. Nulliparous patients with no major medical or surgical history and with normal ovarian function, who meet the legal criteria for medically assisted reproduction, represent the best indications for UTx at this stage of its development.